Clinical Outcomes After Microfracture of the Knee: Midterm Follow-up. Issue 2 (6th February 2018) - Weber, Alexander E.; Locker, Philip H.; Mayer, Erik N.; Cvetanovich, Gregory L.; Tilton, Annemarie K.; Erickson, Brandon J.; Yanke, Adam B.; Cole, Brian J.
Background: Microfracture is a single-stage arthroscopic procedure used to treat small- and medium-sized cartilage defects, the clinical results of which have been mixed to date. Purpose: To retrospectively evaluate prospectively collected patient-reported outcomes (PROs) after microfracture as well as to determine patient-related and defect-related factors associated with clinical outcomes and which factors predict the need for additional surgery. Study Design: Case-control study; Level of evidence, 3. Methods: All patients between the ages of 10 and 70 years who underwent microfracture by the senior author for a focal chondral defect of the knee between January 1, 2005, and March 1, 2010, were eligible for study enrollment. Patients were excluded if they underwent concomitant procedures that violated the subchondral bone. Functional outcomes were determined using preoperative and final follow-up PROs, including the Lysholm, International Knee Documentation Committee (IKDC), Knee injury and Osteoarthritis Outcome Score (KOOS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Short Form–12 (SF-12), and overall satisfaction scores. Patient-related factors (sex, age, body mass index [BMI]) and defect-related factors (lesion size, location, concomitant procedures, prior procedures) were analyzed for correlations with outcome scores. All patient-related and defect-related factors were also analyzed as predictors for subsequent surgery. Results: Overall, 101 patients (102 knees; 55 male, 46 female; mean age, 35.87 ± 12.52 years; mean BMI, 26.3 ± 5.5 kg/m 2 ; mean defect size, 2.635 ± 1.805 cm 2 ) were included. Lesion location included 44.90% at the medial femoral condyle, 21.43% at the trochlea, 11.22% at the lateral femoral condyle, 10.20% at multiple sites, 8.16% at the patella, and 4.08% at the tibial plateau. Microfracture was performed alone in 72 of 102 (71%) knees. At a mean follow-up of 5.66 ± 2.54 years (range, 2-11 years), clinically meaningful and statistically significant improvements were seen in all PROs ( P < .05) except the SF-12 mental component score. Patients who had an isolated tibial plateau defect or multiple defects demonstrated reduced improvements in the symptom rate ( P = .0237). Patients with a BMI >30 kg/m 2 had lower postoperative scores on the KOOS activities of daily living subscale ( P = .0261) and poorer WOMAC function and WOMAC pain scores ( P = .029 and .0307, respectively). Patient BMI, age, sex, defect location, concomitant procedures, and operative side were not significant predictors for additional surgery. Larger defect size (>3.6 cm 2 ) and prior knee surgery were independent risk factors for additional knee surgery after microfracture. Conclusion: After microfracture, all PROs demonstrated clinically and statistically significant improvements at 5.7 years. Functionally, male patients benefited more from microfracture than female patients. Microfracture of tibial lesions and multisite microfracture provided less benefit than microfracture of isolated femoral defects. Larger lesion size (>3.6 cm 2 ) and prior knee surgery predicted the need for additional knee surgery after microfracture.